UNLOCKING SOCIAL EMPOWERMENT: A STUDY ON THE TRANSFORMATIVE ROLE OF MICROFINANCE SERVICES IN EMPOWERING MARGINALIZED GROUPS - Vishnu P K; Anil P V (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study explores the role of microfinance services in enhancing the social empowerment of marginalized groups in Kerala, focusing on two major components: micro savings and microcredit. The respondents are members of Self-Help Groups (SHGs) who belong to Scheduled Castes (SC), Scheduled Tribes (ST), and Persons with Disabilities (PwDs). A total of 180 SHG members were selected through a multi-stage random sampling method, and the data were analyzed using Structural Equation Modeling (SEM). The findings show that both micro savings and microcredit have a positive and statistically significant influence on social empowerment, although the strength of these effects is relatively modest. Micro savings demonstrated a small but meaningful impact, suggesting that regular saving habits and access to secure savings platforms help improve financial discipline and planning, which supports empowerment. Similarly, microcredit showed a modest positive effect, indicating that access to small loans may boost financial independence and community participation. However, microcredit alone is unlikely to bring about major social change without additional support. The results emphasize the need for an integrated approach to microfinance. To make it more effective, financial services should be combined with non-financial support such as financial literacy programs, entrepreneurship training, and community capacity-building. Overall, the study finds that microfinance emerges not only as a tool for poverty reduction but also as a means for empowerment and inclusion. It enables marginalized individuals to participate actively in society and lead lives with dignity. These insights can help guide policymakers and practitioners in promoting inclusive development.